Pharmacokinetic and pharmacodynamic analyses of cocaine and its metabolites in behaviorally divergent inbred mouse strains - Zhu, Jing (Genes Brain Behav, 2020)
Cocaine is a psychostimulant with a high potential for abuse and addiction. Risk for cocaine use disorder is driven, in part, by genetic factors. Animal models of addiction-relevant behaviors have proven useful for studying both genetic and non-genetic contributions to drug response. In a previous study, we examined initial locomotor sensitivity to cocaine in genetically diverse inbred mouse strains. That work highlighted the relevance of pharmacokinetics in initial locomotor response to cocaine but was limited by a single dose and two sampling points. The objective of the present study was to characterize the pharmacokinetics and pharmacodynamics of cocaine and its metabolites (norcocaine and benzoylecgonine) in 6 inbred mouse strains (I/LnJ, C57BL/6J, FVB/NJ, BTBR T+ tf/J, LG/J, LP/J) that exhibit extreme locomotor responses to cocaine. Mice were administered cocaine at one of 4 doses and concentrations of cocaine, norcocaine, and benzoylecgonine were analyzed in both plasma and brain tissue at 5 different time points. Initial locomotor sensitivity to cocaine was used as a pharmacodynamic endpoint. We developed an empirical population PK model that simultaneously characterizes cocaine, norcocaine, and benzoylecgonine in plasma and brain tissues. We observed interstrain variability occurring in the brain compartment that may contribute to pharmacodynamic differences amongst select strains. Our current work paves the way for future studies to explore strain-specific pharmacokinetic differences and identify factors other than pharmacokinetics that are responsible for the diverse behavioral response to cocaine across these inbred mouse strains.